2008
DOI: 10.1177/1049731508318658
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Parent Training in Child Welfare: Maintenance and Booster Training

Abstract: Previous research has demonstrated the efficacy of a 30-hr behavioral parent training program at increasing skill accuracy. However, it remains unknown whether skills acquisitions are maintained on a long-term basis. Few studies have evaluated the maintenance of skills learned during behavioral parent training for foster parents. The purpose of this study is twofold: (a) to assess skill maintenance 8 to 35.5 months following the initial 30-hr training program and (b) to evaluate whether a 6-hr booster training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The SF method has demonstrated success in teaching other skills as well (see Jensen & Steiner, 2017). Vollmer and colleagues (Marcus et al, 2001; Van Camp et al, 2008) have applied their training model upon which the SF method is based to multiple skills, though a comparison with alternative methods has not been evaluated. The current method is fairly experimenter-intensive, requiring a trained role player, an individual providing feedback, and one recording data for a single parent in training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SF method has demonstrated success in teaching other skills as well (see Jensen & Steiner, 2017). Vollmer and colleagues (Marcus et al, 2001; Van Camp et al, 2008) have applied their training model upon which the SF method is based to multiple skills, though a comparison with alternative methods has not been evaluated. The current method is fairly experimenter-intensive, requiring a trained role player, an individual providing feedback, and one recording data for a single parent in training.…”
Section: Discussionmentioning
confidence: 99%
“…They found this method to be effective in working with the parents of four children. Other studies have found similar rehearsal and feedback methods to be effective (Berard & Smith, 2008; Cobb, Leitenberg, & Burchard, 1982; Van Camp et al, 2008), but no comparisons of the training procedure to other methods have been explored.…”
mentioning
confidence: 99%
“…Van Camp, Vollmer, et al (2008) documented that caregivers who completed the program demonstrated substantial improvements in the targeted skills from pretest to posttest role-play evaluations. However, Van Camp, Montgomery, et al (2008) found decreases in role-play performance at 8–35 months after the course had ended. The authors then demonstrated that a brief booster training immediately restored performance to the previously attained levels.…”
mentioning
confidence: 85%
“…Behavioral parent training is an empirically supported intervention that has shown to be effective in the reduction of noncompliant child behavior and the acquisition of effective parenting skills in a number of settings, populations, and social problems (Briggs et al, 2005; Smagner & Sullivan, 2005; Stoutimore, Williams, Neff, & Foster, 2008; van Camp, Montgomery, et al, 2008; van Camp, Vollmer, et al, 2008). For example, the basic philosophy, principles, and methodologies of behavioral parent training have demonstrated utility in analyzing and addressing issues encountered by families with child welfare involvement, foster parents, and other caregivers of children in custody (Azar & Siegel, 1990; Azar & Wolfe, 1996; Barth et al, 2005; Lutzker, 1990; Pinkston et al, 1982; Smagner & Sullivan, 2005; van Camp et al, 2008). However, there is a continued need for studies to evaluate the efficacy or effectiveness of behavioral parent trainings on foster parents’ acquisition of parenting competencies and skills and families with child welfare involvement (Barth et al, 2005; van Camp et al, 2008).…”
Section: Behavioral Parent Trainingmentioning
confidence: 99%
“…For example, the basic philosophy, principles, and methodologies of behavioral parent training have demonstrated utility in analyzing and addressing issues encountered by families with child welfare involvement, foster parents, and other caregivers of children in custody (Azar & Siegel, 1990; Azar & Wolfe, 1996; Barth et al, 2005; Lutzker, 1990; Pinkston et al, 1982; Smagner & Sullivan, 2005; van Camp et al, 2008). However, there is a continued need for studies to evaluate the efficacy or effectiveness of behavioral parent trainings on foster parents’ acquisition of parenting competencies and skills and families with child welfare involvement (Barth et al, 2005; van Camp et al, 2008). Other scholars have reviewed the behavior parent training program literature and found that the programs are also well established with parents who experience coercive and disruptive child behavior problems (Marcus, Swanson, & Vollmer, 2001; McMahon & Wells, 1998; O’Dell, 1985).…”
Section: Behavioral Parent Trainingmentioning
confidence: 99%